Existence and uniqueness for an m-point boundary value problem at resonance on infinite intervals - Liu, B.; Li, J.; Liu, Lishan (Pergamon Press, 2012)
This paper investigates an m-point boundary value problem with nonlinear boundary conditions at resonance on infinite intervals. By establishing a general continuation theorem, the existence and uniqueness of unbounded solutions is obtained on the basis of a suitable homotopy, Leray-Schauder degree properties and a priori estimate. This paper provides a new method to solve boundary value problems with nonlinear boundary conditions at resonance on infinite intervals. © 2012 Elsevier Ltd. All rights reserved.